The Kaposi Sarcoma Herpesvirus latency-associated nuclear antigen DNA binding domain dorsal positive electrostatic patch facilitates DNA replication and episome persistence - Li, Shijun (2022)
© 2015 ASBMB. Currently published by Elsevier Inc; originally published by American Society for Biochemistry and Molecular Biology.